When cost-effective interventions are unaffordable: Integrating cost-effectiveness and budget impact in priority setting for global health programs - Bilinski, Alyssa; Neumann, Peter; Cohen, Joshua; Thorat, Teja; McDaniel, Katherine; Salomon, Joshua A. (PLOS Medicine, 2017)
KerkoCite.ItemAlsoKnownAs: 10.1371/journal.pmed.1002397 2339240:DPDBP8UV 2405685:G3W2NWX3

Supporting Parenting through Differentiated and Personalized Text-Messaging: Testing Effects on Learning During Kindergarten - Doss, Christopher; Fahle, Erin; Loeb, Susanna; York, Ben (2017)
Recent studies have shown that texting-based interventions can produce educational benefits in children across a range of ages. These studies vary in their focus from broad curricula on child development, to reminders about missing work, to steps needed in order to enroll in college. Given the potential effectiveness of texting, as well as the ease of systematically varying
KerkoCite.ItemAlsoKnownAs: 2339240:9AKV6UFP 2405685:RWQG2ZYP 2405685:WL2K529Q
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Do School Electriﬁcation and Provision of Digital Media Deliver Educational Beneﬁts? First-year Evidence from 164 Tanzanian Secondary Schools - Seo, Hee Kwon (University of Chicago, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:9XWPHF2H 2405685:DPI4T7LU

Expenditures and Revenue Management - Morrell, Lance (2017)
KerkoCite.ItemAlsoKnownAs: 2339240:LW7XXDQC 2405685:LIVD2ABR

Interrogating Gender Divides in Technology for Education and Development: the Case of the One Laptop per Child Project in Ghana - Steeves, Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
shortDOI: 10/ggtsmj KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 10/ggtsmj 2339240:DKVPCJ4N 2405685:EBIDU596 2405685:EHX857GT
Keywords: C: Ghana

Through the Looking Glass: Can Classroom Observation and Coaching Improve Teacher Performance in Brazil? - Bruns, Barbara; Costa, Leandro; Cunha, Nina (World Bank Group, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:GTWNV6MT 2405685:U2D68PYR
Keywords: ___working_potential_duplicate

Use of digital game based learning and gamification in secondary school science: The effect on student engagement, learning and gender difference - Khan, Amna; Ahmad, Farzana Hayat; Malik, Muhammad Muddassir (Education and Information Technologies, 2017)
This study aimed to identify the impact of a game based learning (GBL) application using computer technologies on student engagement in secondary school science classrooms. The literature reveals that conventional Science teaching techniques (teacher-centered lecture and teaching), which foster rote learning among students, are one of the major concerns in Pakistan Education system. This leads to student disengagement in science lessons eventually resulting in student absenteeism and dropouts from the schools. This study consisted of five stages: (1) examining the impact of Digital Game-Based Learning (DGBL) and gamification on engagement, learning and gender difference, and literature related to using DGBL models for instructional design; (2) planning learning activities and developing a GBL application based on a specific content in Science; (3) conducting an intervention with a sample of 72 participants of 8th grade (aged 12–15) in a low cost private school of Pakistan following quasi-experimental research framework; (4) observing behaviour and emotions of the participants during science lessons; (5) conducting pre and post tests to assess the learning outcomes of participants followed by focus groups discussion. Analysis from Friedman test, Mann-Whitney U test, and Wilcoxon Signed Rank test show that the GBL application has a positive influence on student engagement. However, GBL application was not equally effective for all students since girls outperformed boys in terms of engagement and learning outcomes. This study gives insights into the development of better educational games to promote student learning.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-017-9622-1 2339240:8MNNLVNL 2405685:629DUKTV

Inclusive Quality Education for Children with Disabilities - Singal, Nidhi; Ware, Hannah; Bhutani, Sweta Khanna (World Innovation Summit for Education & University of Cambridge, 2017)
KerkoCite.ItemAlsoKnownAs: 2339240:4ZA5WMI7 2339240:VS2APB8E 2339240:WALVDQHQ 2405685:B7XYHF4V 2405685:G784RVFY 2405685:UHVMVWIX

Interrogating gender divides in technology for education and development: The case of the one laptop per child project in Ghana - Steeves, H. Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
15 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1007/s12116-017-9245-y 2339240:4VMARDY3 2405685:S4AUFT59
Keywords: Development; Gender; Ghana; Information communication technology (ICT); Internet; ⛔ No INSPIRE recid found

Innovation in education: what works, what doesn’t, and what to do about it? - Serdyukov, Peter (Journal of Research in Innovative Teaching & Learning, 2017)
Purpose The purpose of this paper is to present an analytical review of the educational innovation field in the USA. It outlines classification of innovations, discusses the hurdles to innovation, and offers ways to increase the scale and rate of innovation-based transformations in the education system. Design/methodology/approach The paper is based on a literature survey and author research. Findings US education badly needs effective innovations of scale that can help produce the needed high-quality learning outcomes across the system. The primary focus of educational innovations should be on teaching and learning theory and practice, as well as on the learner, parents, community, society, and its culture. Technology applications need a solid theoretical foundation based on purposeful, systemic research, and a sound pedagogy. One of the critical areas of research and innovation can be cost and time efficiency of the learning. Practical implications Several practical recommendations stem out of this paper: how to create a base for large-scale innovations and their implementation; how to increase effectiveness of technology innovations in education, particularly online learning; how to raise time and cost efficiency of education. Social implications Innovations in education are regarded, along with the education system, within the context of a societal supersystem demonstrating their interrelations and interdependencies at all levels. Raising the quality and scale of innovations in education will positively affect education itself and benefit the whole society. Originality/value Originality is in the systemic approach to education and educational innovations, in offering a comprehensive classification of innovations; in exposing the hurdles to innovations, in new arguments about effectiveness of technology applications, and in time efficiency of education.
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/JRIT-10-2016-0007 2339240:H2BGZB69 2405685:R3REETEJ
Keywords: Educational technology; Implementation; Innovation; Time efficiency

Promoting Student–Teacher Interactions: Exploring a Peer Coaching Model for Teachers in a Preschool Setting - Johnson, Stacy R.; Finlon, Kristy J.; Kobak, Roger; Izard, Carroll E. (Early Childhood Education Journal, 2017)
Peer coaching provides an attractive alternative to traditional professional development for promoting classroom quality in a sustainable, cost-effective manner by creating a collaborative teaching community. This exploratory study describes the development and evaluation of the Colleague Observation And CoacHing (COACH) program, a peer coaching program designed to increase teachers’ effectiveness in enhancing classroom quality in a preschool Head Start setting. The COACH program consists of a training workshop on coaching skills and student-teacher interactions, six peer coaching sessions, and three center meetings. Pre-post observations of emotional support, classroom organization, and instructional support using the Classroom Assessment Scoring System of twelve classrooms assigned to peer coaching were compared to twelve control classrooms at baseline and following the intervention. Findings provide preliminary support that the peer coaching program is perceived as acceptable and feasible by the participating preschool teachers and that it may strengthen student–teacher interactions. Further program refinement and evaluation with larger samples is needed to enhance student–teacher interactions and, ultimately, children’s adaptive development.
shortDOI: 10/gbjks7 KerkoCite.ItemAlsoKnownAs: 10.1007/s10643-016-0790-1 10/gbjks7 2405685:5SRMZ3SD
Keywords: Classroom quality; Head Start; Peer coaching; Professional development; Professional learning communities; Student–teacher interactions